Confirmatory Factor Analysis of the French Version of the Savoring Beliefs Inventory - Golay, Philippe; Thonon, Bénédicte; Nguyen, Alexandra; Fankhauser, Caroline; Favrod, Jérôme (Frontiers in Psychology, 2018)
The Savoring Beliefs Inventory (SBI) is a measure designed to assess attitudes towards savoring positive experience within three temporal orientations: the past (reminiscence), the present moment (present enjoyment) and the future (anticipation). The aim of this study was to validate the structure of the SBI – French version. The scale was tested with 335 French-speaking participants. Two models were estimated: a one-factor model representing a general construct of savoring and a three-factor model differentiating between anticipation, present enjoyment and reminiscence. Several indicators of model fit were used: the root mean square error of approximation (RMSEA), the comparison fit index (CFI), the Tucker–Lewis fit index (TLI) and the standardized root mean residual (SRMR). A chi-square difference test was used to compare the two models. The model fit of the three-factor model assessed by the SRMR showed to be excellent, while it could be considered as satisfactory according to the CFI and TLI coefficients. RMSEA, however, was slightly less adequate. The model fit for the one-factor model seemed less adequate than the three-factor solution. Further, the chi-square difference test revealed that the three-factor model had significantly better fit than the one-factor model. Finally, the reliability of the four scores (anticipating pleasure, present moment pleasure, reminiscing pleasure, and total score) was very good. These results show that the French version of the SBI is a valid and valuable scale to measure attitudes regarding the ability to savor positive experience, whether it be in anticipation, reminiscence or the present moment.